Respuesta :

The given series is geometric with common ratio [tex]6^x - 9[/tex], which converges if [tex]|6^x - 9|<1[/tex] (i.e. the interval of convergence). We have the well-known result

[tex]\displaystyle |r| < 1 \implies \sum_{n=0}^\infty ar^n = \frac{a}{1-r}[/tex]

If you're not familiar with that result, it's easy to reproduce.

Let [tex]S_N[/tex] be the [tex]N[/tex]-th partial sum of the infinite series,

[tex]\displaystyle S_N = \sum_{n=0}^N \left(6^x - 9\right)^n = 1 + \left(6^x - 9\right) + \left(6^x - 9\right)^2 + \cdots + \left(6^x - 9\right)^N[/tex]

Multiply both sides by the ratio.

[tex]\left(6^x - 9\right) S_N = \left(6^x - 9\right) + \left(6^x - 9\right)^2 + \left(6^x - 9\right)^3 + \cdots + \left(6^x - 9\right)^{N+1}[/tex]

Subtract this from [tex]S_N[/tex] to eliminate all the powers of the ratio between 0 and [tex]N+1[/tex].

[tex]\left(1 - \left(6^x - 9\right)\right) S_N = 1 - \left(6^x - 9\right)^{N+1}[/tex]

Solve for [tex]S_N[/tex].

[tex]S_N = \dfrac{1 - \left(6^x - 9\right)^{N+1}}{10-6^x}[/tex]

Now as [tex]N\to\infty[/tex], the exponential term converges to 0 and we're left with

[tex]\displaystyle \sum_{n=0}^\infty \left(6^x-9\right)^n = \lim_{N\to\infty} S_N = \boxed{\frac1{10-6^x}}[/tex]